Design and rationale of randomized evaluation of decreased usage of beta-blockers after acute myocardial infarction (REDUCE-AMI). Issue 2 (13th December 2022) - Yndigegn, Troels; Lindahl, Bertil; Alfredsson, Joakim; Benatar, Jocelyne; Brandin, Lisa; Erlinge, David; Haaga, Urban; Held, Claes; Johansson, Pelle; Karlström, Patric; Kellerth, Thomas; Marandi, Toomas; et al.
Abstract: Aims: Most trials showing benefit of beta-blocker treatment after myocardial infarction (MI) included patients with large MIs and are from an era before modern biomarker-based MI diagnosis and reperfusion treatment. The aim of the randomized evaluation of decreased usage of beta-blockers after acute myocardial infarction (REDUCE-AMI) trial is to determine whether long-term oral beta-blockade in patients with an acute MI and preserved left ventricular ejection fraction (EF) reduces the composite endpoint of death of any cause or recurrent MI. Methods and results: It is a registry-based, randomized, parallel, open-label, multicentre trial performed at 38 centres in Sweden, 1 centre in Estonia, and 6 centres in New Zealand. About 5000 patients with an acute MI who have undergone coronary angiography and with EF ≥ 50% will be randomized to long-term treatment with beta-blockade or not. The primary endpoint is the composite endpoint of death of any cause or new non-fatal MI. There are several secondary endpoints, including all-cause death, cardiovascular death, new MI, readmission because of heart failure and atrial fibrillation, symptoms, functional status, and health-related quality of life after 6–10 weeks and after 1 year of treatment. Safety endpoints are bradycardia, AV-block II-III, hypotension, syncope or need for pacemaker, asthma or chronic obstructive pulmonary disease, and stroke. Conclusion: The results from REDUCE-AMI will add important evidence regarding the effect of beta-blockers in patients with MI and preserved EF and may change guidelines and clinical practice. Graphical Abstract: